![image](https://tex.z-dn.net/?f=sin%282x%29%2B2cos%28x-%5Cfrac%7B%5Cpi%7D%7B2%7D%29%3D%5Csqrt%7B3%7Dcos%28x%29%2B%5Csqrt%7B3%7D%5C%5C2sin%28x%29cos%28x%29%2B2sin%28x%29%3D%5Csqrt%7B3%7D%28cox%28x%29%2B1%29%5C%5C2sin%28x%29%28cos%28x%29%2B1%29-%5Csqrt%7B3%7D%28cos%28x%29%2B1%29%3D0%5C%5C%28cos%28x%29%2B1%29%282sin%28x%29-%5Csqrt%7B3%7D%29%3D0%5C%5C%5Cleft+%5B+%7B%7Bcos%28x%29%3D-1%7D+%5Catop+%7Bsin%28x%29%3D%5Cfrac%7B%5Csqrt%7B3%7D%7D%7B2%7D%7D%7D%5Cright.%3C%3D%3E%5Cleft+%5B+%7B%7Bx%3D-%5Cpi%2B2%5Cpi%5Cn%3B%5Cn%E2%88%88Z%7D+%5Catop+%7Bx%3D%28-1%29%5Ek%5Cfrac%7B%5Cpi%7D%7B3%7D%2B%3Cspan%3E%5Cpi%5C%3C%2Fspan%3En%3B%5Cn%E2%88%88Z%7D%7D%5Cright.)
\left [ {{x=-\pi+2\pi\n;\n∈Z} \atop {x=(-1)^k\frac{\pi}{3}+
\pi\n;\n∈Z}}\right." alt="sin(2x)+2cos(x-\frac{\pi}{2})=\sqrt{3}cos(x)+\sqrt{3}\\2sin(x)cos(x)+2sin(x)=\sqrt{3}(cox(x)+1)\\2sin(x)(cos(x)+1)-\sqrt{3}(cos(x)+1)=0\\(cos(x)+1)(2sin(x)-\sqrt{3})=0\\\left [ {{cos(x)=-1} \atop {sin(x)=\frac{\sqrt{3}}{2}}}\right.<=>\left [ {{x=-\pi+2\pi\n;\n∈Z} \atop {x=(-1)^k\frac{\pi}{3}+
\pi\n;\n∈Z}}\right." align="absmiddle" class="latex-formula">
По решению в общем в виде не сложно будет отобрать корни